Pengembangan Media Pada Mata Pelajaran IPA Materi Tumbuhan Untuk Siswa - Tristaningrat, Made Adi Nugraha; Mahartini, Komang Trisna (Edukasi: Jurnal Pendidikan Dasar, 2023)
The purpose of this research is to produce products from the development of plant material media for elementary/MI students. This research uses research and development methods which use the development model procedure developed by Borg & Gall. In this research, the author limits it to the product development process. The dissemination process and large-scale testing will be written separately in another article. From this development, a product was produced in the form of media that uses the Articulate Storyline 3 application which can combine graphics and animation so it is very suitable for elementary school students. The use of computer-based technology is a way to produce or convey material using technology-based sources, where the information or material presented is stored in digital form. The author is here to provide a solution through the development of media related to plant material that can overcome problems for elementary school students.